Advances in research regarding the roles of non-coding RNAs in non-syndromic cleft lip with or without cleft palate: A systematic review. (February 2022) - Wei, Yuanyuan; Tian, Yu; Yu, Xin; Miao, Ziyue; Xu, Yan; Pan, Yongchu
Abstract: Objective: To investigate by means of a literature review, what non-coding RNAs engage in non-syndromic cleft lip with or without cleft palate (NSCL/P) and how they lead to the occurrence of this malformation. Design: A literature search of online databases (Medline via PubMed, Web of Science, Scopus, and Embase) was performed using appropriate keywords (e.g. non-coding RNA, miRNA, lncRNA, NSCL/P, non-syndromic cleft lip only, and non-syndromic orofacial cleft). The risk of bias in the included studies was then assessed, and a comprehensive review of reported non-coding RNAs associated with NSCL/P was performed. Results: The initial search retrieved 133 studies reporting non-coding RNAs associated with NSCL/P; after excluding 18 replicates and 77 ineligible studies, 35 remained. Of these, 16 studies fulfilled all the criteria and were included in the systematic review. These studies established the roles of non-coding RNAs in the development of craniofacial structures. The differential expression of these non-coding RNAs could lead to orofacial clefts, indicating their significance in NSCL/P and their profound research value. Conclusion: There is evidence that non-coding RNAs are involved in the formation of NSCL/P. Specifically, they play significant roles in the regulation of genes and signalling pathways related to NSCL/P. Highlights: ● Non-coding RNAs engage in non-syndromic cleft lip with or without cleft palate formation. ● Non-coding RNAs could form complicated networks to regulate the gene expression. ● Non-coding RNAs could influence the cell cycle of epithelium and its fusion.